Effect of oral feeding of Allium schoenoprasum L. on blood glucose and lipid level in diabetic Rats - Roghani M (PhD); Khalili M (PhD); Baluchnejadmojarad (PhD); Aghaie M; Ansari F (BSc); Sharayeli M (BSc) (مجله دانشگاه علوم پزشکی گرگان, 2010)
Background and Objective: Reduction of serum glucose and lipids in diabetic patients due to medicinal plants is clinically very important. Therefore, the effect of Allium schoenoprasum feeding on blood glucose and lipids was investigated in male streptozotocin-diabetic Rats. Materials and Methods: In this experimental study, male Wistar Rats (n=32) were divided into 4 groups, i.e. control, Allium schoenoprasum -treated control, diabetic, and Allium schoenoprasum -treated diabetic groups. The treatment groups received oral administration of plant-mixed pelleted food at a weight ratio of 6.25% one week after the study for 6 weeks. For induction of diabetes, streptozotocin was administered at a dose of 60 mg/kg (i.p.). Serum glucose and lipids levels were determined before the study and at 3rd and 6th weeks after the study. Results: Serum glucose was significantly lower in Allium schoenoprasum -treated diabetic Rats at 3rd and 6th weeks as compared to untreated diabetics (p<0.05). In addition, serum total cholesterol did not show a significant change at 6th week in Allium schoenoprasum -treated diabetic Rats as compared to untreated diabetics. There was also a significant lower level of triglyceride in Allium schoenoprasum -treated diabetic Rats (p<0.05) and Allium schoenoprasum treatment caused significant improvement in HDL- and LDL- cholesterol levels in treated diabetic group as compared to untreated diabetic group (p<0.05). Conclusion: This study showed that oral administration of Allium schoenoprasum to streptozotocin-diabetic Rats at a food weight ratio of 6.25% has a significant hypoglycemic effect, reduces serum triglyceride and LDL-cholesterol level and increases serum HDL-cholesterol.